Fenomena Boikot Produk Pro Israel: Peran Media Sosial, Religiusitas, dan FOMO terhadap Brand Switching Pada Generasi Z - Lutfia Izdhihar Qotrunnada (Journal of Economics and Business Research (JUEBIR), 2024)
The purpose of this study is to examine how brand switching decisions among generation Z related to the boycott of pro-Israel products are influenced by social media, religiosity, and Fomo. A quantitative approach was taken in this study, and 100 respondents were given a questionnaire to complete to collect data. To ensure appropriate respondents, this study used a non-probability sampling technique combined with a purposive sampling technique. Multiple linear regression was used to assess the relationship between variables in the information analysis. The findings of the study indicate that brand switching is not significantly influenced by social media, indicating that information shared on social media does not directly affect customer choices. In contrast, religiosity and Fomo were tested to have a significant influence on brand switching. The conclusion of this study confirms that brand switching decisions in the context of the boycott of pro-Israel products by generation Z are more influenced by internal factors, such as religiosity and Fomo, than by the influence of social media. These findings provide a new contribution to the consumer behavior literature by highlighting the significant role of Fomo in influencing brand switching decisions among generation Z.